The Howe Brothers and the American Revolution - Gruber, Ira D. (UNC Press enduring editions., 2015)
By focusing on the Howe brothers, their political connections, their relationships with the British ministry, their attitude toward the Revolution, and their military activities in America, Gruber answers the frequently asked question of why the British failed to end the American Revolution in its early years. This book supersedes earlier studies because of its broader research and because it elucidates the complex personal interplay between Whitehall and its commanders.